METODE-METODE PENDIDIKAN ISLAM DALAM MENDIDIK ANAK-ANAK - Muhamad Khoirur Roziqin (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2017)
ABSTRACT Talking about the issue of education, however the form of education, both education in general and Islamic education in particular will not be separated by the learning process. Education is a conscious and well-planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have spiritual spiritual power, self-control, personality, intelligence, noble character, as well as the skills needed of him and society. Islamic religious education is the most important part of family education to form the human kamil. In guiding or educating a child let parents use the method or way, so that the education provided can affect the child. In this case the method has an important role in the process of character formation. Islamic education method as a regular and systematic way of working and thinking of all the factors that exist to achieve the goal of Islamic religious education. Key Words: Islamic Education, Methods, Children